2017
DOI: 10.1093/nar/gkx1008
|View full text |Cite
|
Sign up to set email alerts
|

HCMDB: the human cancer metastasis database

Abstract: Metastasis is the main event leading to death in cancer patients. Over the past decade, high-throughput technologies have provided genome-wide view of transcriptomic changes associated with cancer metastases. Many microarray and RNA sequencing studies have addressed metastases-related expression patterns in various types of cancer, and the number of relevant works continues to increase rapidly. These works have characterized genes that orchestrate the metastatic phenotype of cancer cells. However, these expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 50 publications
1
94
0
Order By: Relevance
“…Three lists of cancer-related proteins were scanned with the final ML prediction model: 1232 CIPs were taken from Patel et al [37], 1903 MDPs were taken from the Human Cancer Metastasis Database (HCMDB) (http://hcmdb.i-sanger.com/index) [68], and 1369 RBPs were taken from Hentze et al , [41, 68] (Tables S3-S5).…”
Section: Methodsmentioning
confidence: 99%
“…Three lists of cancer-related proteins were scanned with the final ML prediction model: 1232 CIPs were taken from Patel et al [37], 1903 MDPs were taken from the Human Cancer Metastasis Database (HCMDB) (http://hcmdb.i-sanger.com/index) [68], and 1369 RBPs were taken from Hentze et al , [41, 68] (Tables S3-S5).…”
Section: Methodsmentioning
confidence: 99%
“…The PPi network was performed to better understand the behavior of hypoxia-related proteins in cancer and metastasis using the String Database and Cytoscape (Figure 7 (Table S25). Additionally, top ten proteins with the highest degree centrality in the HIF-1 signaling pathway were AKT1, PIK3CA, HIF1A, VEGFA, EGFR, EP300, CREBBP, STAT3, On the other hand, the Human Cancer Metastasis Database (HCMDB) is an integrated database designed to analyze large scale expression data of cancer metastasis 59 . Our PPi network was conformed by 179 (62%) metastatic driver proteins ( Figure 7) (Table S26).…”
Section: Protein-protein Interactome Networkmentioning
confidence: 99%
“…Metastasis driver proteins that interact with the hypoxia-related proteins were taken from the Human Cancer Metastasis Database (https://hcmdb.i-sanger.com/). HCMDB is an integrated database designed to analyze large scale expression data of cancer metastasis 59 . The network visualization was analyzed through the Cytoscape software 58 .…”
Section: Protein-protein Interactome Networkmentioning
confidence: 99%
“…Besides functional annotations, public literature retrieval further provided associated evidence for the specific functions of these target genes in tumor metastasis. Through the human cancer metastasis database, 10 which contained systematically collected transcriptome data and manually curated publications related to human cancer metastasis, we found that 107 target genes had been demonstrated to be related to the metastasis of multiple types of cancer ( Figure 6C).…”
Section: Functional Enrichment Analysis Of Downstream Target Genesmentioning
confidence: 99%